Emmanuel Levinas: between captivity and philosophy (2009)
The article takes up again some aspects of the life and work of Emmanuel Levinas. It focuses on the period of his captivity (1940-1945), in which he wrote De la existencia al existente. The author proposes that De la existencia al existente shows not only